(3GdaJGhi GdYOdjIs - (3GdCjOjfj, QShd Hf UGdM, J (B978 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdMeO ddg Pj GdLdGd hGdEcQGe , hGdUdGI Ydi eMeO NjQ GdCfGe hYdi Bdg hCUMGHg GdYXGes
(3BNQgG (B:s
(3cPG aj bGVjNGf hddhUj Cf jhOY eGd GdjJje hjHVY hjJLQ HeGd GdjJje hjOaY YWi QHg hdg Cf jaYd cd eG ajg NjQg ddjJjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 714s
(3cTa GdXfhf (B2 / 1226s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfHdjs